2021
DOI: 10.3389/fneur.2021.714820
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 7-Tesla Imaging of Cortical Myelin Changes in Early Multiple Sclerosis

Abstract: Cortical demyelination occurs early in multiple sclerosis (MS) and relates to disease outcome. The brain cortex has endogenous propensity for remyelination as proven from histopathology study. In this study, we aimed at characterizing cortical microstructural abnormalities related to myelin content by applying a novel quantitative MRI technique in early MS. A combined myelin estimation (CME) cortical map was obtained from quantitative 7-Tesla (7T) T2* and T1 acquisitions in 25 patients with early MS and 19 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Similar to what was seen in WM assessments, ODI highlighted inconsistent results. In included studies, this measure was decreased in cortical and GM lesions 28,35 and unchanged in cortical lesions 24,30 when compared with NAGM and NGM. In comparison to NGM of HC, one study showed elevated ODI of NAGM, 25 two showed null results of ODI changes in NA cortex, 24,26 and three reported decreased ODI in NA cortex and NAGM 28,35,36 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar to what was seen in WM assessments, ODI highlighted inconsistent results. In included studies, this measure was decreased in cortical and GM lesions 28,35 and unchanged in cortical lesions 24,30 when compared with NAGM and NGM. In comparison to NGM of HC, one study showed elevated ODI of NAGM, 25 two showed null results of ODI changes in NA cortex, 24,26 and three reported decreased ODI in NA cortex and NAGM 28,35,36 .…”
Section: Resultsmentioning
confidence: 95%
“…In included studies, this measure was decreased in cortical and GM lesions 28,35 and unchanged in cortical lesions 24,30 when compared with NAGM and NGM. In comparison to NGM of HC, one study showed elevated ODI of NAGM, 25 two showed null results of ODI changes in NA cortex, 24,26 and three reported decreased ODI in NA cortex and NAGM 28,35,36 . All the studies assessing ISOVF demonstrated no alterations in cortical lesions 30 and NA cortex 30,37 in affected people.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly CME abnormalities were not coupled by changes in neurite orientation dispersion and density imaging (NODDI) [42], a measure of neurite/dendrite loss, supporting the hypothesis that CME changes were mostly driven by demyelination. At the same time, areas of increased CME could imply elevated arborization of the dendrites in repairing lesions [43 ▪▪ ]. In a larger MS cohort, NODDI modeling demonstrated that overall, cortical lesions identified at 3 T present a significant reduction of neurite density and orientation dispersion index, possibly due to a simplification of neurite complexity [44 ▪▪ ].…”
Section: In Vivo Features Of Cortical Lesionsmentioning
confidence: 99%
“…The perivenous lesion development or central vein sign in multiple sclerosis (MS) has been revealed in vivo for the first time, 2 which has proved useful for a differential diagnosis of MS. 3 Seven teslas MRI showed improved detection of cortical MS lesions that are consistent with histopathological patterns of cortical demyelinating lesions regarding their cortical layer involvement that are not seen on 3 T MRI. 4 The visibility of small venous architecture, including small cortical and medullary veins, has an important implication for tissue oxygen utilization and neuronal degeneration. 5 By introducing an ultrasmall-superparamagnetic-iron-oxide (USPIO) contrast agent (e.g., ferumoxytol), the small arterioles can also be seen on 7 T SWI, which allows the detection of small arterial tortuosity in the elderly, likely the major cause of small vessel disease.…”
mentioning
confidence: 99%